Discrete Element Modeling and Electron Microscopy Investigation of Fatigue-Induced Microstructural Changes in Ultra-High-Performance Concrete - Sebastian Rybczynski (MDPI AG, 2021)
In view of the growing demand for sustainable and lightweight concrete structures, the use of ultra-high-performance concrete (UHPC) is becoming increasingly important. However, fatigue loads occur more frequently in nature than static loads. Despite the impressive mechanical properties of UHPC, a reduced tolerance for cyclic loading is known. For this reason, our paper deals with experimental and numerical investigations regarding the main causes for crack initiation on the meso, micro, and nanoscale. After mechanical fatigue tests, we use both scanning (SEM) and transmission electron microscopy (TEM) to characterize microstructural changes. A new rheological model was developed to apply those changes to the mesoscopic scale. The origins of fatigue damaging can be traced back to a transformation of nanoscale ettringite, resulting in a densification of the surrounding binder matrix. Additionally, a higher content of unhydrated cement clinker in the matrix benefits fatigue resistance. On the mesoscale, stress peaks around aggregate grains expand into the surrounding binder with increasing load cycles and lead to higher degradation.